The The Effect Of Profitability, Size And Liquidity on Firm Value in Consumer Goods Industry Listed on The Indonesia Stock Exchange (IDX) - Candra Kurnia Saputri; Axel Giovanni (Profesional Muda Cendekia Publishing, 2021)
This research was conducted with the aim of knowing the effect between profitability, size and liquidity on firm value in consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2018. This research was conducted because there are still differences in research results and there is fluctuation in the value of the company in the consumer goods industry sector companies listed on the Indonesia Stock Exchange. The population used in this study were companies in the consumer goods industry listed on the IDX in the 2014 - 2018 period. While the sample used in this study were 37 companies in the consumer goods industry sector which were selected using the purposive sampling method. The data analysis technique used is multiple regression analysis in order to determine the relationship between variables. The results of this study indicate that profitability, size and liquidity simultaneously have an influence on firm value. Partially profitability has a positive and significant effect on firm value, size has no effect on firm value and liquidity has a negative and significant effect on firm value.